282 CERVICAL ESOPHAGECTOMY USING "LARYNX ROTATION METHOD" CAN OBTAIN GOOD CLINICAL OUTCOMES. (14th September 2020) - Nakajima, Y; Ogiya, K; Endo, H; Okada, T; Hoshino, A; Kawada, K; Saeki, I; Takahashi, S
Abstract:  : In the treatment of cervical esophageal carcinoma (CEC), preservation of laryngeal function is required as well as curability. Therefore, chemoradiotherapy (CRT) is often selected for larynx-preservation. In our department, larynx-preserving surgery using "larynx-rotation method" is aggressively carried out even when the oral side of the tumor margin extends beyond the esophageal orifice. In this study, we analyzed the clinical outcomes of the resectable CEC and examined ``Which therapeutic modality should be selected, surgery or CRT?'' Methods: In the present study, 40 patients whose primary tumor was resectable Stage II/III CEC treated in our department since 2008, whose advanced primary tumor lesion was limited within cervical esophagus, and who undergo surgery or curative CRT were enrolled. The clinical outcomes were retrospectively analyzed. Results: The Op group included 25 patients. All of the Op group patients could preserve the larynx. In the CRT group, 2 patients were performed pharyngo-laryngo-cervical esophagectomy as the salvage surgery. 1- and 3-year progression-free survival rate was 80.1 and 69.3% in the Op group, and 63.0 and 31.5% in the CRT group. 1-, 3- and 5-year overall survival rate was 95.8, 80.9 and 67.4% in the Op group and 78.6, 64.3 and 46.9% in the CRT group, respectively. Although there was no significant difference, the Op group showed relatively better clinical outcomes. Conclusion: Cervical esophagectomy using "larynx-rotation method" could obtain good therapeutic outcomes while preserving the larynx. Especially in case cervical esophagectomy is sufficient as the curative resection, because the surgical invasion is little and the postoperative quality of life is good while preserving the larynx and the whole stomach, surgery is considered useful treatment modality.